'A Europe without Walls, without Fences, without Borders': A Desecuritisation of Migration Doomed to Fail. (November 2018) - Skleparis, Dimitris
It has been commonly argued that amid the so-called 'migration crisis' in 2015, Greece ignored its Dublin Regulation obligations due to unprecedentedly high migration flows, structural weaknesses, fears and uncertainty. However, this narrative deprives the Greek government of agency. In contrast, this article puts forward an alternative analysis of Greece's attitude. It argues that the Greek government's policy choices in the realms of border controls, migration and asylum in 2015, prior to the 'EU–Turkey deal', manifested a well-calculated desecuritisation strategy with a twofold aim. In this respect, this article provides an analysis of why and how the newly elected SYRIZA-led coalition government embarked on a desecuritising move and assesses the success/effectiveness of this move and the desecuritisation strategy. It argues that although the government's desecuritising move was successful, overall, its desecuritisation strategy failed to produce the anticipated results vis-à-vis the government's twofold aim and intended outcomes.